Effect of Kangaroo Mother Care on hospital management indicators: A systematic review and meta-analysis of randomized controlled trials - Mahdi Jafari (Journal of Education and Health Promotion, 2019)
Results of previous studies about the effect of Kangaroo Mother Care (KMC) on hospital management indicators (HMIs) (length of stay [LOS], readmission to hospital, parent satisfaction, and parent's preference for same postdelivery care) had high confusions. The aim of this study was to conduct a systematic review and meta-analysis of randomized controlled trials on the effect of KMC on HMI in comparison with the conventional neonatal care (CNC). In this systematic review and meta-analysis study, required data were collected by searching the following keywords: “length of stay,” “readmission to hospital,” satisfaction,” same post-delivery,” “hospital management,” indicators, “skin-to-skin,” “Kangaroo Mother Care,” randomized trial. The following databases were searched: Google Scholar, PubMed, EMBASE, Scopus, and Cochrane. To estimate the hospital management indicators, computer software Comprehensive Meta-Analysis 2 was used. Finally, 18 articles were included to analysis. The overall LOS standard different between groups (KMC vs. CNC) was − 0.91 days (95% confidence interval [CI], −2.14–0.32, Q = 25.6, df = 10, P = 0.004, I2 = 60.98). The overall readmission to hospital standard different between groups was − 1.78% (95% CI, −1.21%–0.86%, Q = 0.024, df = 1, P = 0.87, I2 = 0.00). The overall parent satisfaction standard different between groups was 5.3% (95% CI, −32.4%–43%, Q = 0.052, df = 2, P = 0.97, I2 = 0.00). The overall standard different between groups was 16.2% (95% CI, −24.7%–57.1%, Q = 0.040, df = 1, P = 0.84, I2 = 0.00). KMC improves HMI but not significantly. According to the current study result and other studies that report positive effect of KMC on health status of the newborns and parents, implemented of KMC in low- and middle-income countries recommended.